ADAPTIVE MODEL OF INDUSTRIAL SAFETY IN THE SITUATIONAL MANAGEMENT SYSTEM - Polyanska, Alla Stepanivna; Микитюк, Олег Романович (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2025)
The article considers the theoretical and methodological principles of industrial safety management of an enterprise in the context of situational management. It is substantiated that the modern industrial safety management model is adaptive, since it must take into account the requirements of the internal and external environment. An integrated industrial safety system that can potentially be used by an enterprise is considered and presented, which covers standards and systems and defines their role in industrial safety management. A conceptual and analytical model of situational industrial safety management (SIMSM) is developed, which differentiates approaches to risk management, resilience and response in the war period, in the transition phase and during post-war recovery. The model consists of 3 levels - situational, operational and strategic adaptation block. The adaptive management zone integrated into the model in the middle of the operational block combines safety, continuity and resilience, transferring decisions from reactive to proactive, closes the feedback loop with a learning loop. The methodological framework is made up of the requirements of the business continuity management system based on traditional and modern international and domestic safety management standards. A four-stage procedure for industrial safety management is proposed based on the identification of external and internal factors and weak signals for three time phases; determination of critical processes and impact thresholds with risk assessment; design of ISMS with the allocation of the stages “data-models-rules-decisions-KPI-feedback” with sets of actions for each phase; justification of leadership styles in the logic of situational leadership of Hersey-Blanchard. Based on the development of theoretical safety concepts, a scheme for industrial safety management based on weak signals is considered, which consists of sequential stages that allow industrial safety management based on a sequential data processing cycle taking into account deviations and escalations, which ultimately makes the management process transparent, understandable and manageable. A combination of weak signal management with a business continuity management cycle based on international quality standards and linked to situational leadership styles according to the time frames "war-transition-recovery" is proposed.